Realizing the Dream of Teaching Girlhood Studies. Issue 3 (1st December 2022) - Mitchell, Claudia
Abstract : A dream, dating back to 2001 when the late Jackie Kirk, Jacqui Reid-Wash, and I passed through a section labelled Girls Studies in Foyles Books on Charing Cross Rd., London, UK, was that someday there would not only be a journal devoted to girlhood studies but also a whole interdisciplinary teaching area. We talked about how students of youth studies, or childhood studies, or what was then called women's studies might consider girlhood studies as an option in their programs or as a whole area of specialization. The dream of the journal was realized seven years later with the first issue of Girlhood Studies in 2008. Since then, as the guest editors of this Special Issue on Teaching Girlhood Studies highlight, there have been many initiatives including the development of courses on Girlhood Studies, and community/university activist projects. And now, finally, we have a whole issue devoted to teaching, curricula, and pedagogies of Girlhood Studies.